S. Krymsky: man at the joint of ages and values - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with S.B. Krymsky’s prediction upon the existence of mankind on the turn of the millennium, and the prospects for itsadaptation to the new era.